Pemberdayaan Perempuan Desa Tanjung Seteko melalui Pelatihan Pembuatan Lulur Berbasis Ampas Kopi - Poedji Loekitowati Hariani; Muhammad Said; Dedi Rohendi; Eva Musifa; Herlina Herlina (PELITA NUSA TENGGARA, 2026)
Body scrubs are a widely used skincare product among mothers and young women. The use of natural resources as a primary component in body scrubs is gaining increasing attention. This community service activity aims to provide training in making body scrubs from coffee grounds. Coffee was chosen because it contains bioactive compounds that have antioxidant and antibacterial activity. The activity was carried out in Tanjung Seteko Village, Indralaya District, Ogan Ilir Regency, involving 30 participants, including mothers and young women. The activity method was carried out through counseling, training, and activity evaluation. Participants actively participated throughout the activity, both in the counseling session and in the practical session of making body scrubs from coffee grounds. Evaluations were conducted before and after the training to measure the participants' level of understanding of the material provided. The evaluation results showed an increase in the level of understanding of participants after the training, as indicated by a shift in the category from not understanding and less understanding in the pretest to understanding and very understanding in the posttest. Through this community service activity, the community increasingly understands that skin care can be done using natural ingredients that are safer and have no risk of side effects. The community responded positively to the body scrub product in terms of color, aroma, texture, consistency, and appeal.